Density-Functional Methods for Excited States - Ferré, Nicolas; Filatov, Michael; Huix-Rotllant, Miquel; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
The series Topics in Current Chemistry presents critical reviews of the present and future trends in modern chemical research. The scope of coverage is all areas of chemical science including the interfaces with related disciplines such as biology, medicine and materials science. The goal of each thematic volume is to give the non-specialist reader, whether in academia or industry, a comprehensive insight into an area where new research is emerging which is of interest to a larger scientific audience. Each review within the volume critically surveys one aspect of that topic and places it within the context of the volume as a whole. The most significant developments of the last 5 to 10 years are presented using selected examples to illustrate the principles discussed. The coverage is not intended to be an exhaustive summary of the field or include large quantities of data, but should rather be conceptual, concentrating on the methodological thinking that will allow the non-specialist reader to understand the information presented. Contributions also offer an outlook on potential future developments in the field. Review articles for the individual volumes are invited by the volume editors. Readership: research chemists at universities or in industry, graduate students.
From the Contents: Current status and recent developments in linear response TD-DFT -- Density matrix functional theory (DMFT) and linear response time-dependent DMFT (TD-DMFT) for excited states -- Ensemble DFT for strongly correlated molecules and excited states.
Keywords: Chemistry, Physical and theoretical; Physical chemistry; Spectrum analysis; Theoretical Chemistry; Physical Chemistry; Spectroscopy